Egg Production and Calcium-Phosphorus Utilization of Laying Hens Fed Diets Supplemented with Phytase Alone or in Combination with Organic Acid - Sari, Mustafa; Onol, Ahmet G.; Daskiran, Mehmet; Cengiz , Ozcan (International Journal of Poultry Science, 2012)
An experiment was conducted to determine the effects of dietary organic acid and phytase supplementation on performance and calcium and phosphorus utilization in laying hens. Two hundred 23-wk-old Brown Nick layers were randomly allocated into 50 cages (42 x 50 cm) each containing 4 birds. Each dietary treatment had 5 replications and each replication comprised two adjacent cages. Corn-soybean meal based rations were used. Five dietary treatments were formed as followed: (1) a basal ration with no supplemental P (negative control, NC) (2750 kcal ME/kg, 17% CP, 0.34% total P, 3.8% Ca), (2) basal ration supplemented with dicalcium phosphate (1.4%) (positive control, PC), (3) basal ration supplemented with 0.035% phytase (ZY Phytase II-5, NC+P), (4) basal ration supplemented with 1.0% organic acid (Salstop SD, NC+OA) and (5) basal ration supplemented with both 0.035% phytase and 1.0% organic acid (NC+POA). Water and feed were provided for ad libitum consumption and a lighting program of 16 h light : 8 h dark was applied throughout the study. NC treatment resulted in body weights that were lower (p